Arnold Rikli (1823-1906), utemeljitelj klimatskega zdravilišča na Bledu - Toplak, Cirila (Medicinski razgledi, 1998)
This paper was written to mark the 175th anniversary of birth of Arnold Rikli,famous Swiss healer, who is credited with pioneering modern health tourism in Slovenia. In 1855, Rikli settled in the alpine region of Lake Bled to set up a health resort. His treatment methods which adhered to principles of natural healing exploited the favourable effects of light, air and water onthe human body. The Bled health resort attracted rich people with various ailments who came there to be treated in special, almost ,"revolutionary" ways. Rikli's treatment methods met with strong opposition of both local community and mainstream medicine, but some of his principles are still valid today.
Keywords: Health resorts; Rikli, Arnold, 1823-1906; zdravilišča; Climate; Bled